Predicting preeclampsia course based on endothelium-dependent dilation - R.Kh. Shavaeva; A.V. Murashko; V.M. Zuev; S.A. Timofeev; T.A. Dzhibladze (LCC «Medicine-Inform», 2021)
R.Kh. Shavaeva, A.V. Murashko, V.M. Zuev, S.A. Timofeev, T.A. Dzhibladze I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation Aim: to determine prognostic criteria of severe preeclampsia based on the assessment of endothelium-dependent (ED) flow-mediated dilation (FMD) of the brachial artery (BA). Patients and Methods: 97 pregnant women (>28 weeks of pregnancy) with moderate preeclampsia were enrolled. These women were retrospectively divided into two groups. Group 1 included 42 pregnant women (mean age 30.0±0.5 years) in whom the severity of preeclampsia increased after treatment. Group 2 included 55 pregnant women (mean age 31.0±0.7 years) whose severity of preeclampsia did not increase after treatment. Group 3 (control group) included 20 women with a healthy pregnancy. ED FMD of BA was assessed by vascular ultrasound using a reactive hyperemia test. In addition, BA diameter and peak systolic velocity (PSV) 15 sec and 1 min after cuff deflation were measured. These measurements were performed at enrollment and after one week (or in feeling worse). Results: healthy pregnancy was characterized by a gradual increase in BA diameter in response to cuff inflation (by 15.7% and 23.9% after 15 sec and 1 min, respectively, at baseline and by 17.8% and 21.3% after 15 sec and 1 min, respectively, after one week). In pregnant women with preeclampsia, baseline changes in BA diameter were less significant. Meanwhile, after one week, a reduction in BA diameter was reported in group 1, and close-to-normal BA diameter was reported in group 2. In group 3, BA PSV increased by 5.2% and 16% in 15 sec and 1 min, respectively, after cuff inflation. In pregnant women with preeclampsia, BA PSV, in contrast, was reduced (more significant after 1 min). Conclusion: increased BA diameter and PSV by less than 10% 15 sec and 1 min after cuff inflation indicate endothelial dysfunction. A negative pattern of changes in these parameters suggests an unfavorable course of preeclampsia and its transition to severe disease. Keywords: preeclampsia, e ndothelial dysfunction, vasodilation, brachial artery, peak systolic velocity, prognosis. For citation: Shavaeva R.Kh., Murashko A.V., Zuev V.M. et al. Predicting preeclampsia course based on endothelium-dependent dilation. Russian Journal of Woman and Child Health. 2021;4(4):317-321 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-317-321.